IMPLEMENTATION OF ANDROID LEARNING MEDIA TO TRAIN STUDENTS' MOTOR WRITING SKILLS - Ghazia Rahmi Sahid; Prana Dwija Iswara; Dety Amelia Karlina (Jurnal Cakrawala Pendas, 2024)
Motor skills are natural abilities that are used throughout life. However, at this stage of student development, there needs to be increased development of motor skills. Not all students' motor development processes are the same. From the results of observations, several children experienced delays in writing motor skills, especially when writing. Researchers took action that was influential in treating fine motor disorders in students, namely handwriting therapy by applying Android learning media in the form of the ABC Kids application to class III students at SDN Sukaraja I Sumedang. This research implemented a one group pretest-posttest design with a total of 19 students as research subjects. The data analysis technique used in this research is quantitative descriptive analysis. The research was conducted for 3 days. The first two days showed that students still did not know letters and could not write well, and on the third day students began to show the ability to recognize letters and write well. The results of the normality test show that a value of sig=.0013 is obtained, which means it is smaller than a 0.05, which indicates that the data is not normally distributed with a small number of samples, so a non-parametric statistical test is carried out. In the Wilcoxon test, a significant value of .000 is obtained < 0.05, so the hypothesis is accepted. The results of the research show that there are differences in the fine motor development abilities of students before and after being given the ABC Kids application to lower class students in elementary school.